Wheat plants sense substrate volume and root density to proactively modulate shoot growth. (28th December 2020) - Wheeldon, Cara D.; Walker, Catriona H.; Hamon‐Josse, Maxime; Bennett, Tom
Abstract: Plants must carefully coordinate their growth and development with respect to prevailing environmental conditions. To do this, plants can use a range of nutritional and non‐nutritional information that allows them to proactively modulate their growth to avoid resource limitations. As is well‐known to gardeners and horticulturists alike, substrate volume strongly influences plant growth, and maybe a key source of non‐nutritional information for plants. However, the mechanisms by which these substrate volume effects occur remain unclear. Here, we show that wheat plants proactively modulate their shoot growth with respect to substrate volume, independent of nutrient availability. We show that these effects occur in two phases; in the first phase, the dilution of a mobile 'substrate volume‐sensing signal' (SVS) allows plants to match their shoot (but not root) growth to the total size of the substrate, irrespective of how much of this they can occupy with their roots. In the second phase, the dilution of a less mobile 'root density‐sensing signal' (RDS) allows plants to match root growth to actual rooting volume, with corresponding effects on shoot growth. We show that the effects of soil volume and plant density are largely interchangeable and that plants may use both SVS and RDS to detect their neighbours and to integrate growth responses to both volume and the presence of neighbours. Our work demonstrates the remarkable ability of plants to make proactive decisions about their growth, and has implications for mitigating the effects of dense sowing of crops in agricultural practice. Abstract : Plants can measure both substrate volume and root density using mobile signals, which allows them to modify their shoot growth to match the size of their soil volume and neighbour density, and thereby avoid resource limitations later in life.